Oral and Dental Complications of Head and Neck Radiotherapy and their Management - Mod, D; Mod, H; Jha, A (Journal of Nepal Health Research Council, 2014)
Cancer patients who are diagnosed early and or receive effective anti tumour therapy can expect to live for many years after treatment and therefore preservation of normal tissue function is crucial to ensure long term quality of life.Oral complications affect hundred per cent of patients who receive radiotherapy to fields involving the oral cavity and combined modality treatment with chemotherapy may compound these effects. Oral cavity is highly susceptible to side effects as radiotherapy targets cells that divide rapidly and the cells of the mucosal lining of the mouth are rapidly dividing cells and they are thus injured. All patients who are to receive radiotherapy to the head and neck region should be sent for a dental consultation prior to the initiation of their treatment in order to decrease the acute and chronic post treatment sequelae.Keywords: Dental management; head and neck cancers; radiotherapy.